Critical Pedagogy, Race, and Media : Diversity and Inclusion in Higher Education Teaching. - Flynn, Susan; Marotta, Melanie A. ([Place of publication not identified] : Routledge, 2021)
Critical Pedagogy, Race, and Media investigates how popular media offers the potential to radicalise what and how we teach for inclusivity. Bringing together established scholars in the areas of race and pedagogy, this collection offers a unique approach to critical pedagogy by analysing current and historical iterations of race onscreen. The book forms theoretical and methodological bridges between the disciplinary fields of pedagogy, equality studies and screen studies to explore how we might engage in and critique screen culture for teaching about race. It employs Critical Race Theory and paradigmatic frameworks to address some of the social crises in higher education classrooms, forging new understandings of how notions of race are buttressed by popular media. The chapters draw on popular media as a tool to explore the social, economic and cultural dimensions of racial injustice, and are grouped by Black studies, migration studies, Indigenous studies, Latinx studies, and Asian studies. Each chapter addresses diversity and the necessity for teaching to include visual media which is reflective of a myriad of students' experiences. Offering opportunities for using popular media to teach for inclusion in higher education, this critical and timely book will be highly relevant for academics, scholars, and students across interdisciplinary fields such as pedagogy, human geography, sociology, cultural studies, media studies, and equality studies.
List of FiguresList of Contributors AcknowledgmentsForeword Jessica BermanIntroductionSusan Flynn and Melanie A. MarottaReading Race in Film: Birth of a Nation and Django Unchained Jonathan WrightNarratives of Institutional Racism and Social Critique in UK Television Drama Teresa Forde Imagining Difference Differently: Digital and Decolonial Diffractions of Power, Race and Materiality in (Post)Pandemic EducationAnnouchka BayleyTeaching an Inclusive English Composition Course: The Vampire GenreMelanie A. MarottaRefugee 2.0- (De)constructing race, ethnicity and identity through digital cultures in refugee campsClaudia BöhmeReframing the Refugee Discourse: Countervisual analysis of migrants' self-representational strategies in contemporary media Boris RuzicPlaying Difference: Toward a Games of Colour PedagogyKishonna L. Gray; Ashlee Bird and Edmond Y. Chang Reading and Writing to Reclaim Humanity: Centering the Ongoing History of Asian Exclusion in America in the (Digital) Age of Covid-19 Kathleen Tamayo AlvesWhose Bollywood is this anyway?: Exploring Critical Frameworks for Studying Popular Hindi Cinema Shweta Rao GargTribalWays:How toTeach Indigenous Studies withoutTextbooksBrian Wright-McLeodColor-Blindness and Neoliberalism in Disney's Pocahontas Brennan Thomas Building on the Burial Ground: Reflecting on the Impacts of Native American Representation in 1980's American HorrorLisa Ellen WilliamsGaming from the margins: Indigenous representation, critical gaming, and pedagogy Wendi Sierra Questioning the Drug War Frame: Teaching Mexico's Violence through Documentary Representations of Race David Shames"Chicken Noodle Soup" with Critical Race Theory on the Side Kristen Lillvis and Ivy Scoville
Keywords: Critical pedagogy; Race relations; EDUCATION / Multicultural Education